Assistive device for efficient intravitreal injections - Mathis-Ullrich, Franziska; Michels, Stephan; Lehmann, Daniel; Pieters, Roel S.; Becker, Matthias D.; Nelson, Bradley J. (Ophthalmic surgery, lasers & imaging retina, 2016)
Ophthalmic Surgery, Lasers and Imaging Retina | Intravitreal therapy is the most common treatment for many chronic ophthalmic diseases, such as age-related macular degeneration. Due to the increasing worldwide demand for intravitreal injections, there exists a need to render this medical procedure more time- and cost-efficient while increasing patient safety. The authors propose a medical assistive device that injects medication
Gesehen am 29.05.2020